If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -2x = x + -6 Reorder the terms: 9 + -2x = -6 + x Solving 9 + -2x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + -2x + -1x = -6 + x + -1x Combine like terms: -2x + -1x = -3x 9 + -3x = -6 + x + -1x Combine like terms: x + -1x = 0 9 + -3x = -6 + 0 9 + -3x = -6 Add '-9' to each side of the equation. 9 + -9 + -3x = -6 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = -6 + -9 -3x = -6 + -9 Combine like terms: -6 + -9 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 2p-p=3p-16 | | 7(8x-2)-5x=-218 | | 32*60=4500 | | x/5=12 | | 0.3y-0.55=0.05 | | -2=8.6 | | 15x=6x+33 | | 5x+5=2x+35 | | -5-5x=1-6x-x | | 3x=6/7 | | 7/6=3x | | -6n+7n=-2n-n-12 | | 5x-100(4x(5))=176(6x) | | 2-x=x-4 | | 13x=8x+25 | | 3x+2x+4x=108 | | 10=3t-2 | | -17=-2n+13-8m | | 5+3+5x-x=2x-6 | | -7=-2n+13-8m | | 0.5x+1.5=5 | | 14+n-4+3=1+7n | | x+3+x+2+x+4=108 | | 3c^2-8c+2=c(3c-8) | | 2x+40=6x-20 | | 4m+16=-4 | | -3x+4=8+1-x+7 | | 2x+-9=9x | | 5x+2=-12 | | [x-4]=-3 | | 2x-1x=1x-4 | | 10+q=-11 |